Evolution game model of offense-defense for network security based on system dynamics - Jian-ming ZHU; Biao SONG; Qi-fa HUANG (Tongxin xuebao)
An offense-defense game model with learning mechanism in the case of asymmetric information was proposed based on non-cooperation evolution game theory.Combined with utility function,the existence and uniqueness of Nash equilibrium in the offense-defense process were proved.Simulation by system dynamics shows that there is Nash equilibrium in evolutionary game model after introducing the dynamic penalty strategy of the third party.Therefore,when improving all kinds of security technology,promoting attacker tracing technology,enhancing the censorship of network attack behaviors and dynamic penalty are fundamental ways to information security.